2022
DOI: 10.21037/tcr-21-2559
|View full text |Cite
|
Sign up to set email alerts
|

Serum gamma-glutamyl transpeptidase-to-platelet ratio (GPR) can predict the prognosis of hepatocellular carcinoma: a meta-analysis and systematic review

Abstract: Background:The relationship between serum gamma-glutamyl transpeptidase-to-platelet ratio (GPR) before treatment and the prognosis of patients with hepatocellular carcinoma (HCC) is unclear. Here, we review and summarize existing data and try to determine the predictive value of GPR in the treatment of HCC.Methods: We searched Web of Science, PubMed, Embase and China national knowledge infrastructure (CNKI) for clinical trials investigating GPR and HCC in participants with and without HCC. We developed the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The conclusions drawn between different studies are also inconsistent, and the best cutoff values are also different. [18][19][20] In addition, some previous studies have suggested that aminotransferase-to-platelet ratio (APRI) [21][22][23] and gamma-glutamyl transferase-to-platelet ratio (GPR) [24][25][26] are independent risk factors for shorter survival and higher recurrence after HCC surgery. However, it is still uncertain whether preoperative APRI or GPR can predict MVI in solitary HCC, and there is no report on the relationship between APRI/GPR and MVI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions drawn between different studies are also inconsistent, and the best cutoff values are also different. [18][19][20] In addition, some previous studies have suggested that aminotransferase-to-platelet ratio (APRI) [21][22][23] and gamma-glutamyl transferase-to-platelet ratio (GPR) [24][25][26] are independent risk factors for shorter survival and higher recurrence after HCC surgery. However, it is still uncertain whether preoperative APRI or GPR can predict MVI in solitary HCC, and there is no report on the relationship between APRI/GPR and MVI.…”
Section: Introductionmentioning
confidence: 99%
“…39 Several previous studies have shown that APRI and GPR were independent risk factors for shorter OS and high recurrence after HCC surgery. [21][22][23][24][25][26] Additionally, a recent meta-analysis (4706 HCCs) showed a significant correlation between preoperative GPR and postoperative prognosis in HCC patients, with higher GPR closely associated with poorer OS (HR: 1.79; P<0.001). 26 However, MVI is the most direct predictive signal for early intrahepatic micrometastasis in HCC and the most important source of tumor recurrence or poor prognosis.…”
mentioning
confidence: 99%
“…A previous meta-analysis and systematic review published in April 2022 indicated the prognostic impact of GPR on HCC [25]. However, this study evaluated the specificity and sensitivity of GPR for predicting the prognosis of HCC and it evaluated only 1952 patients from seven studies.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies demonstrated that indicators from blood routine test and biochemical examination might be used for prognostic prediction of cancers [ 14–16 ]. For almost all cancer patients, blood routine and biochemical examination are convenient, quick, and inexpensive examinations, from which the information about human metabolism, inflammation, and internal environmental conditions can be obtained.…”
Section: Introductionmentioning
confidence: 99%